Antioxidant potencies and chemical compositions of essential oils of two endemic species grow in Turkey: Astragalus oocephalus subsp. stachyophorus and Astragalus sericans - Geçibesler, İbrahim Halil; Behcet, Lutfi; Erdogan, Mehmet Kadir; Askın, Hakan (Progress in Nutrition, 2017)
Astragalus species are both economic and medicinal plants that are used in the world for years. We investigated essential oil compositions and antioxidant activities of the essential oils from dried aerial parts of two endemic Astragalus taxa, which are Astragalus sericans Freyn & Sint. (AS) and Astragalus oocephalus Boiss subsp. stachyophorus Hub.-Mor. & Chamb. (AOS). The essential oils isolated by Clevenger apparatus and GC-FID and GC-MS analysis resulted in the identification of twenty seven and thirty nine compounds representing 94.79 and  96.76 % of the total oil, respectively. The main compounds were α-Pinene (19.18%), 1,5,5-Trimethyl-6-methylene-cyclohexene (16.34%), and 2,5,5-Trimethyl-1,3,6-heptatriene (9.64%) in A. sericans essential oil, whereas Camphor (18.25%), γ-Terpineol (16.74%), 1,8-Cineole (16.35%), and α-Pinene (12.82%) were the major constituents of A. oocephalus subsp. stachyophorus. It was concluding that the essential oils; α-Pinene chemotype in A. sericans and Camphor chemotype in A. oocephalus subsp. stachyophorus was in plants from eastern Anatolian region of Turkey. Inhibition of lipid peroxidation was 70.36±0.75% for AS and 37.22±0.23% for AOS at concentration of 200 µg/ml. Reducing powers of essential oils and their scavenging effects were effective when compared with Vit. E and BHT. IC50 values were 44.43±1.09 µg/ml for AS and 134.22±1.31 µg/ml for AOS. These essential oils can be used in medicinal and pharmaceutical purposes.